The Teaching Role of the Tutor and Training Supervisor in Social Work: Building Introspection and Commitment During Training via Supervision - Puig-Cruells, Carmina (Prospectiva. Revista de Trabajo Social e Intervención Social, 2020)
This article delves deep into the fundamental themes of training for social workers and has as its basis the article “The Teaching Role of the Training Supervisor and Accompaniment of the Student” written in 2004. The original article was written driven by the necessity to clearly define the teaching roles of tutors and supervisors in internship practices.Its reiterated use in pedagogy, as well as its contributions to understanding the complexity of relationships which are formed during internships, make it, even today, a text which is frequently consulted and cited.Nevertheless, the inevitable and enriching advance in thought, together with the evolution of social contexts, demand its revision, expansion and even, reformulation.The text that is currently presented contains some of the original concepts which have been up-dated for relevance today, and at the same time, presents new proposals for a deeper study into practical training. It expands and widens the conceptualization and methodology of supervision within the framework of universities as an area for reflection and review of the practices in terms of both technical and curricular development. The article also explores the various roles in greater depth as well as the teaching tasks of both the tutor and supervisor as they accompany the student. Although the article makes new contributions to the field, a number of paragraphs will need to be understood with reference to the past, the era in which they were written.